Site mutation of residues in a loop surrounding the active site of a Psingle bondI snake venom metalloproteinase abrogates its hemorrhagic activity - Camacho Umaña, Erika (2019)
Abrogation of the hemorrhagic activity of BaP1, a PI Snake Venom Metalloproteinase (SVMP) from the venom of Bothrops asper, was achieved by the substitution of residues in the first part of the U loop surrounding the active site by the corresponding residues of a structurally-similar non-hemorrhagic PI SVMPfromarelated venom. Previous studies by molecular dynamic simulation showed higher flexibility in the first part of the loop in hemorrhagic SVMPs, as compared to non-hemorrhagic SVMPs. It has been suggested that the U loop is critical for protein-protein interface and may be involved in the interaction with extracellular matrix proteins, hence influencing the ability of the toxin to bind and hydrolyze basement membrane components. The SVMP with the site mutation completely lost hemorrhagic ac tivity, and only had a partial reduction of proteolytic activity, indicating that this region in the loop plays a key role in the ability to induce hemorrhage. Our findings demonstrate a key structural determinant of the hemorrhagic capacity of PI SVMPs.